THE ASSESMENT OF THE RELATION BETWEEN RETENTION OF BACTERIAL BIOFILM AND THE ANATOMO-CLINICAL FEATURES OF CERVICAL AREA - Galina Pancu; Sorin Andrian; Gianina Iovan; Angela Ghiorghe; Claudiu Topoliceanu; Antonia Moldovan; Andrei Georgescu; Irina Nica; Silvia Teslaru; Simona Stoleriu (Romanian Society of Oral Rehabilitation, 2015)
The aim of this study was to identify the anatomo-clinical features of tissues relations in the cervical area and to establish the presence and retention of bacterial biofilm related to the types of cementoenamel junction (CEJ). Material and methods: The study included 16 extracted teeth (4 incisors, 2 canines, 4 bicusps, 6 molars). The teeth, having unaffected cervical area, were cut in 4 sections preserving the bucal, lingual, mesial and distal cervical areas. The dental sections were assessed regarding the aspect and the morphology of the cementoenamel junction using SEM. Also the retention degree of bacterial biofilm was examined. Results: The highest percent (62%) CEJ are represented by the type of edge-to-edge. The bicusps present a percent of 76% of edge-to-edge CEJ, with a 14% percent of CEJ junctions associated with enamel covered by cement. Conclusions The type of cementoenamel junction varies accordingly to dental type and topography. The retention of bacterial biofilm was highest in cementoenamel junctions with exposed dentine.